Entrepreneurial Interest in Vocational School Students - Nabila Khairia; Yarmis Syukur (Counseling and Humanities Review, 2021)
This research is motivated by the lack of interest in entrepreneurship among vocational students. This research aims to describe the entrepreneurial interest of students of SMK N 6 Padang as a whole and by its aspects, namely(1) interest in entrepreneurship, (2) willingness to be involved in entrepreneurial activities, (3) seeing opportunities for entrepreneurship, (4) exploiting the potential for entrepreneurship, (5) courage in facing risks, (6) courage in facing challenges, (7) feeling happy about entrepreneurial activities, and (8) the desire to realize ideals in entrepreneurship. The type of method used is quantitative with a descriptive approach, the population is 274 students of class XII majoring in Culinary, Fashion, and Beauty Design and a sample of 163 people. Data were analyzed using percentage techniques. The research findings show that students' interest in entrepreneurship is in the high category (69.3%) in terms of (1) interest in entrepreneurship, (2) willingness to be involved in entrepreneurial activities, (3) seeing opportunities for entrepreneurship, (4) taking advantage of the potential for entrepreneurship, (5) courage in facing risks, (6) courage in facing challenges, (7) a feeling of pleasure in entrepreneurial activities, and (8) the desire to realize ideals in entrepreneurship.